PRETRIAL BY CURATOR IN BANKRUPTCY PROCESS (A REVIEW OF THE CASE OF DECISION NO. 89 /PID.PRAP/2016/PN.JAKSEL) - Papang Sapari (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
The curator is a party appointed by law through the Decision of the Commercial Court Judge at the District Court in a bankruptcy case to administer Bankruptcy assets. In Law Number 37 of 2004 concerning Bankruptcy and PKPU, the Curator is tasked with increasing the debtor's bankruptcy assets for the benefit of the Creditors as much as possible, but in carrying out these duties, the Curator can be criminalized by both the Creditors and the Debtors themselves. The Bankruptcy Law and PKPU have not guaranteed legal certainty and protection for curators when carrying out their duties. the bankruptcy application process, namely the process of requesting a decision to declare bankruptcy is regulated in Article 6 to Article 11 of the Bankruptcy Law. An application for bankruptcy can only be submitted at the request of one or more applicant subjects who have the legal standing as regulated in Article 2 of the Bankruptcy Law. This application is addressed to the Chairman of the Commercial Court whose jurisdiction includes the area where the debtor's legal domicile is.